2003
DOI: 10.1345/aph.1c069
|View full text |Cite
|
Sign up to set email alerts
|

Branded versus Generic Clozapine for Treatment of Schizophrenia

Abstract: In this small group of patients with schizophrenia, no deterioration in clinical status in several domains was noted after changing from branded to generic clozapine. This finding is consistent with pharmacologic data suggesting bioequivalence of the 2 products. Results, however, must be interpreted cautiously due to the lack of optimal study controls and small sample size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…Therefore, it is extremely unlikely that our design merely failed to detect a small increase in utilization. The lack of an increase in utilization is consistent with previous reports by Makela et al (2003) and Stoner et al (2003) demonstrating that patients switched to generic clozapine did not show a deterioration in clinical status 2-4 months after the switch. Further, Sajbel, Carter, and Wiley (2001) showed a lack of leucopenia or a need to change clozapine dosages when patients were switched to Zenith Goldline Pharmaceuticals clozapine, which is also consistent with our data.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, it is extremely unlikely that our design merely failed to detect a small increase in utilization. The lack of an increase in utilization is consistent with previous reports by Makela et al (2003) and Stoner et al (2003) demonstrating that patients switched to generic clozapine did not show a deterioration in clinical status 2-4 months after the switch. Further, Sajbel, Carter, and Wiley (2001) showed a lack of leucopenia or a need to change clozapine dosages when patients were switched to Zenith Goldline Pharmaceuticals clozapine, which is also consistent with our data.…”
Section: Discussionsupporting
confidence: 91%
“…Most of this data is in the form of case reports, however several of these agents have been examined in a randomized cross-over studies (Lam et al, 2001;Kluznik et al, 2001;Kumet and Gelenberg, 2005) and have indicated a increased risk of symptom relapse when switched to generic. Other studies of clozapine and carbemazepine have not shown a significant deterioration in clinical symptoms following a switch to the generic preparation (Makela et al, 2003;Silpakit et al, 1997). The small literature on this issue to date is, therefore, inconclusive on the matter of bioequivalency between generic and brand name preparations.…”
Section: Discussionmentioning
confidence: 97%
“…Makela et al 52 conducted an observational study of 20 Clozariltreated outpatients with schizophrenia who were switched to generic clozapine. All were reported as being stable on brand-name clozapine for several months.…”
Section: Literature Reviewmentioning
confidence: 99%